Disruption of postnatal folliculogenesis and development of ovarian tumor in a mouse model with aberrant transforming growth factor beta signaling - Yang Gao; Xin Fang; David F. Vincent; David W. Threadgill; Laurent Bartholin; Qinglei Li (BMC, 2017)
Abstract Background Transforming growth factor beta (TGFB) superfamily signaling is implicated in the development of sex cord-stromal tumors, a category of poorly defined gonadal tumors. The aim of this study was to determine potential effects of dysregulated TGFB signaling in the ovary using Cre recombinase driven by growth differentiation factor 9 (Gdf9) promoter known to be expressed in oocytes. Methods A mouse model containing constitutively active TGFBR1 (TGFBR1CA) using Gdf9-iCre (termed TGFBR1-CAG9Cre) was generated. Hematoxylin and eosin (H & E) staining, follicle counting, and immunohistochemistry and immunofluorescence analyses using antibodies directed to Ki67, forkhead box L2 (FOXL2), forkhead box O1 (FOXO1), inhibin alpha (INHA), and SRY (sex determining region Y)-box 9 were performed to determine the characteristics of the TGFBR1-CAG9Cre ovary. Terminal deoxynucleotidyl transferase (TdT) labeling of 3'-OH ends of DNA fragments, real-time PCR, and western blotting were used to examine apoptosis, select gene expression, and TGFBR1 activation. RNAscope in situ hybridization was used to localize the expression of GLI-Kruppel family member GLI1 (Gli1) in ovarian tumor tissues. Results TGFBR1-CAG9Cre females were sterile. Sustained activation of TGFBR1 led to altered granulosa cell proliferation evidenced by high expression of Ki67. At an early age, these mice demonstrated follicular defects and development of ovarian granulosa cell tumors, which were immunoreactive for granulosa cell markers including FOXL2, FOXO1, and INHA. Further histochemical and molecular analyses provided evidence of overactivation of TGFBR1 in the granulosa cell compartment during ovarian pathogenesis in TGFBR1-CAG9Cre mice, along with upregulation of Gli1 and Gli2 and downregulation of Tgfbr3 in ovarian tumor tissues. Conclusions These results reinforce the role of constitutively active TGFBR1 in promoting ovarian tumorigenesis in mice. The mouse model created in this study may be further exploited to define the cellular and molecular mechanisms of TGFB/activin downstream signaling in granulosa cell tumor development. Future studies are needed to test whether activation of TGFB/activin signaling contributes to the development of human granulosa cell tumors.